Large-scale electricity storage utilizing reversible solid oxide cells combined with underground storage of CO2 and CH41. Issue 8 (29th August 2015) - Jensen, S. H.; Graves, C.; Mogensen, M.; Wendel, C.; Braun, R.; Hughes, G.; Gao, Z.; Barnett, S. A.
<x xml:space="preserve">Abstract</x> Electricity storage is needed on an unprecedented scale to sustain the ongoing transition of electricity generation from fossil fuels to intermittent renewable energy sources like wind and solar power.